What's the Smoke For? : And Other Burning Questions about the Liturgy - Van Parys, Johan (Book collections on Project MUSE., 2014)
What are Vespers? Where have the consecration bells gone? Why do some liturgical ministers vest and others don't? Blinking sneakers on altar servers, Christmas trees in January ... what is that all about? These are some of the candid questions that Catholics and others often wonder about the liturgy. In What's the Smoke For? expert liturgist Johan van Parys offers helpful and engaging answers. Based on church teaching and rooted in sound theology, Johan's responses invite inquiring minds to continue to think about what is happening in the church and to be engaged in learning more about liturgy and the arts.